Learning path : SCCM : building concepts with Microsoft System Center Configuration Manager. - Hampson, Gerry; Daalmans, Peter; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"System Center Configuration Manager (ConfigMgr) is the flagship systems management product from Microsoft that provides a comprehensive management solution for computer systems. It provides patch management, OS deployment, remote control, endpoint protection, and many other services. This Learning Path will get you started with this powerful solution and eventually enable you to effectively manage your resources. We'll teach you how to install and configure ConfigMgr, manage your devices, deploy operating systems in the enterprise, deploy and manage applications. Then, you will learn to secure SCCM by configuring public key infrastructure, validating HTTPS mode, and configuring site roles to support HTTPS. Finally, you will learn to manage your Mac OSX using Configuration Manager, where you will be taught how to enroll your Mac device, deploy applications and settings, and explore different third-party applications. By the end of this course you will be well versed with the various advanced, yet real-world scenarios that you may come across using Microsoft System Center Configuration Manager."--Resource description page.
Introducing System Center Configuration Manager / Gerry Hampson -- Advanced Microsoft SCCM current branch scenarios / Peter Daalmans.
Presenters, Gerry Hampson, Peter Daalmans.
Title and publication information from resource description page (Safari, viewed June 1, 2017).
Keywords: Microsoft System center; Computer networks -- Management; Client/server computing; Electronic books